Firms and institutions : the demand for skills and their social production in Europe - Regini, Marino [Verfasser] (My University, 1995)
"It is commonly argued that national economic performance is enhanced by a 'surplus' of workers with extensive and well-developed skills, and that this is best achieved by a training system such as that in Germany, where employers are institutionally inhibited from 'free-riding' on other firms investment in human resources. On the basis of a comparative study of France, Germany, Italy and Spain, the author argues that this is an oversimplification. Firms can choose among a variety of production strategies; and each choice implies a different pattern of workforce composition and training. Training regimes different from the much-vaunted German model can be well suited to specific production and market strategies." (author's abstract, IAB-Doku) ((en)) Der Autor bestreitet die generelle Überlegenheit des deutschen dualen Systems der Berufsausbildung zur Bereitstellung der erforderlichen Basisqualifikationen. Anhand eines internationalen Vergleichs argumentiert er, dass je nach den vorherrschenden personalpolitischen Strategien und Produktionsstrategien auch andere Systeme effizient sein können. (IAB)
Keywords: S 5 Organisationsentwicklung; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; Berufsausbildung; Betriebliche Berufsausbildung; Internationaler Vergleich; Beschäftigerverhalten; Frankreich; Italien; Spanien